Quality of life in Zahedan elderly population - Ahmadi F; Salar A; Faghihzadeh S (Tehran University of Medical Sciences, 2004)
Introduction: It has been estimated that 335 million elderly, about 13 percent of general population, live in developing countries. It has been predicted that in 2040, this percentage will rise to 20 percent. Psychophysical complains are common in elderly and investigation of quality of life (QOL) in these samples of population is very important. Materials and Methods: This research is a descriptive analytical study carried out to investigate the QOL of elderly residents of Zahedan city. In this study a short form questionnaire (SE 36) of QOL was used. Estimated required number of the samples was 200 that were selected with random cluster sampling. Results: Average age of studied population was 72.3 years and their mean number of children was 6.7. Mean scores of the general health perception, physical activity, physical role function, bodily pain, social function, emotional role function, vitality and mental health were 38.6, 42.7, 36.8, 37.8, 43.9, 45,46.7 and 42.7, respectively. Conclusion: Since currently there are no sound data for elderly QOL in Iran, considering mean QOL score of 50 and standard deviation of 10, all observed QOL scores (in eight dimensions) were low. These findings show importance of attention to QOL in elderly clients.